Paclobutrazol in the in vitro conservation of cassava genotypes - Souza, Marcus Dhilermando Hora de; Sá, Jucieny Ferreira de; Mendes, Maria Inês de Souza; Vila Verde, Denise dos Santos; Santos, Karen Cristina Fialho dos; Costa, Maria Angélica Pereira de Carvalho; Souza, Antônio da Silva (Acta Scientiarum. Biological Sciences, 2023)
In vitro germplasm conservation allows to extend the interval between subcultures without compromising the viability and genetic integrity of the plant, ensuring a backup of genotypes with high phytosanitary quality. Thus, this study aimed to verify the effect of four concentrations of Paclobutrazol® in inducing minimum growth in five Manihot esculenta accessions from the in vitro Active Germplasm Bank of Embrapa Cassava and Fruits. An experiment was installed using the Murashige and Skoog medium without addition and added with four concentrations of Paclobutrazol® (0.10, 0.20, 0.30, and 0.40 mg L-1), in five in vitro accessions of M. esculenta: BRS Jari (BGM 2041), Cigana (BGM 0264), BRS Poti Branca (BGM 2017), TME 14, and BRS Novo Horizonte. The statistical design was completely randomized in a 5 x 5 factorial scheme, with 15 repetitions. After 120 days of cultivation, the following variables were evaluated: plant height (cm), number of green leaves, number of senescent leaves, number of mini-cuttings, number of shoots, and fresh and dry mass of shoots and roots (mg). Paclobutrazol® caused a reduction in plant height and gain in root mass for all accessions, in addition to preserving the number of green leaves and decreasing leaf senescence for most genotypes. There was a strong dependence of the genotype in relation to the concentration of Paclobutrazol®. The concentration of 0.20 mg L-1 showed potential in the in vitro conservation of M. esculenta genotypes.